Radiation safety considerations for the bone seeking radiopharmaceuticals - Lam, M. G. E. H.; Hoekstra, A.; de Klerk, J. M. H.; van Rijk, P. P.; Zonnenberg, B. A. (Nuklearmedizin - NuclearMedicine, 2009)
The radiation exposure to bystanders from 89SrCl2, 186Re-HEDP and 153Sm-EDTMP, is generally thought to be caused by “bremsstrahlung” and gamma-radiation, with negligible contribution from beta-radiation. The latter assumption may be erroneous. The aim of this prospective study was the investigation of radiation safety after treatment with these radiopharmaceuticals. The radiation field around treated patients was characterized and the magnitude estimated. Patients, methods: 33 patients (30 prostate carcinoma, 3 breast carcinoma) were treated with 150 MBq 89SrCl2 (9 patients), 1295 MBq 186Re-HEDP (12 patients) or 37 MBq/kg 153Sm-EDTMP (12 patients). External exposure rates at 30 cm from the patient were measured at times 0 to 72 h post-injection. To evaluate the respective contribution of Bremsstrahlung, beta- and gamma-radiation, a calibrated survey meter was used, equipped with a shutter. For each patient, the measured exposure rate-versus-time data were fit to a curve and the curve integrated (area under the curve) to estimate the total exposure. Results: For 29/33 patients the total ambient equivalent doses (mean ± 1 standard deviation [SD]) based on the integral of the fitted curve were 2.1 ± 1.2 mSv for 89SrCl2, 3.3 ± 0.6 mSv for 186Re-HEDP and 2.8 ± 0.6 mSv for 153Sm-EDTMP. Beta-radiation contributes significantly to these doses ( >99% for 89SrCl2, 87% for 186Re-HEDP and 27% for 153Sm-EDTMP). The effective doses (at 30 cm) are < 0.1 mSv for 89SrCl2, 0.3 mSv for 186Re-HEDP and 1.6 mSv for 153Sm-EDTMP. Conclusion: Patients treated with 89SrCl2, 186Re-HEDP or 153Sm-EDTMP emit a spectrum of radiation, including non-negligible beta-radiation. With specific instructions effective doses to bystanders are acceptable.
Keywords: Bone metastases; rhenium; strontium; samarium; radiation safety